THE EFFECT QUALITY TANGERANG LIVE TO PUBLIC SATISFACTION IN TAMAN ROYAL 2 - Rinintha Prameswari (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2020)
This study is intended to determine the Quality Effect of Tangerang Live to Taman Royal Society . Conceptually, Tangerang is one of the cities that would like to apply E-Government through Tangerang Live application. Tangerang Live takes the concept of Smart City where the application has many services to make it easier to serve society of Taman Royal Tangerang and get feed back directly. In service, certain quality is a benchmark regarding whether the government conceptualizes as a smart city can be realized. The purpose is facilitating the society of taman royal Tangerang to get information directly. as well as being criticism and suggestions for Tangerang Government in services. The method used quantitaive which was taken randomly. For quality, it is assumed that the independent variable (x) and satisfaction as the dependent variable (y). The research sample was 80 respondents and the population using the Slovin formula. The results of this study indicates that there is quality effect of Tangerang live to Public Satisfaction. Evidenced by the tcount for the variable (X) of 8.761, while the ttable for n = 80 is 1,990. So 8.761> 1,990, it can be concluded that partially the variable (X) has a positive effect on the variable (Y).